"Fire by Night, Cloud by Day": Exile and Refuge in Postwar London. (January 2020) - Pennybacker, Susan
Abstract: Susan Pennybacker's presidential plenary to the 2017 North American Conference on British Studies in Denver, Colorado, explores the lives of four of the subjects of her book (in progress) of the same title. It identifies the kinds of archival and ethnographic sources that allow new treatments of the exile, émigré, and expatriate communities of London after the close of World War II and of those who contributed in various ways to the ethos of metropolitan political culture in the "late empire" and Cold War era. The essay focuses on the South African Ruth First, the Indian diplomat Mrs. Vijaya Lakshmi Pandit, the Indian academician Achin Vanaik, and the South Asian Londoner Suresh Grover, a member of the Monitoring Group, a legal assistance and anti-discrimination organization in the capital. It suggests the importance of scholarship that reckons with known and notable activist persons who led and represented many others in their challenges to global politics from a base in the "mammoth crossroads, the secure and unsafe haven that is London."